Analisis Pembenihan Ikan Nila Secara Alami di Laboratorium Produksi dan Manajemen Budidaya Perikanan - Shobikhuliatul J Juanda; Heri Murtawan; Alinda Hau Pia (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Nile tilapia (Oreochromis niloticus) is currently one of the most economically important freshwater aquaculture species due to its rapid growth rate, strong disease resistance, and high consumer preference for its flesh. Seed production represents a critical stage in aquaculture, as it directly determines the quality and availability of fish seed for grow-out operations. This Independent Business Project (Proyek Usaha Mandiri/PUM) aimed to examine the techniques of natural Nile tilapia breeding and evaluate the economic feasibility of the hatchery operation conducted at the Aquaculture Production and Management Laboratory of Politeknik Pertanian Negeri Kupang. The project activities included broodstock management, spawning pond preparation, broodstock selection, natural spawning, larval harvesting, feeding management, monitoring of fish growth and water quality, as well as pest and disease control. The results demonstrated that natural breeding under a mass spawning system was capable of producing a large number of uniform fry with a satisfactory survival rate. Economic feasibility analysis, based on fixed costs, variable costs, break-even point (BEP), depreciation, revenue, profit/loss, and the revenue-to-cost (R/C) ratio, indicated that Nile tilapia hatchery operations are economically viable. Therefore, this project not only contributes to the provision of high-quality seed for fish farmers but also offers valuable entrepreneurial opportunities for students pursuing careers in aquaculture.